Discovering the meaning of unknown words in German. Strategies used by university learners - Kienberger, Martina; Vicente Palacios, Víctor (Didáctica. Lengua y Literatura, 2022)
In the present study, free-text responses of 387 German language learners at 19 Spanish universities were analysed from the perspective of the use of strategies related to the discovery of the meaning of new lexical units. The aims of this research were to study how learners describe the strategies they use, which are the most frequently mentioned terms and topics, and whether there are groups or profiles of individuals according to the strategic habits referred to in their comments. For this purpose, natural language processing techniques such as topic modeling were used in combination with cluster analysis methods. In this way, it could be observed that context-based strategies and the use of other languages, especially English, were among the most frequently mentioned. On the other hand, different groups of learners were detected according to their inclination towards a certain type of strategies or a combination of several of them.